Routinely reported 'equivocal' lymphovascular invasion in prostatectomy specimens is associated with adverse outcomes. (31st August 2016) - Galiabovitch, Elena; Hovens, Christopher M.; Peters, Justin S.; Costello, Anthony J.; Battye, Shane; Norden, Sam; Ryan, Andrew; Corcoran, Niall M.
Abstract : Objective: To evaluate the significance of routinely reported 'equivocal' lymphovascular invasion (LVI) in prostatectomy specimens of patients with clinically localized prostate cancer. Materials and Methods: Prospectively collected data from men who underwent prostatectomy for clinically localized prostate cancer were retrospectively reviewed. Rates of adverse pathological features and biochemical recurrence (BCR) were compared between tumours positive, negative or 'equivocal' for LVI. Multivariable Cox regression analysis was performed to identify independent predictors of BCR. Results: Of 1 310 consecutive cases, LVI was present definitively in 82 (6.3%) and equivocally in 43 (3.3%) cases. Similar to definitive LVI, equivocal LVI was significantly associated with other adverse pathological features, including advanced stage, higher Gleason grade and positive surgical margins. BCR occurred more frequently in patients with tumours that were equivocal (61%) or positive for LVI (71%) than in patients with negative results (14.7%). In addition, patients with both definitive and equivocal LVI had a significantly shorter BCR‐free survival time compared with those with negative LVI. Multivariable Cox regression analysis indicated that the presence of either definitive or equivocal LVI were independent predictors of disease recurrence (hazard ratio [HR] 3.32, 95% confidence interval [CI] 2.3–4.8; P <0.001 vs HR 1.66, 95% CI 1.05–2.65; P = 0.032, respectively). Conclusion: In this single‐institution study, equivocal LVI had a similar association with adverse pathological features and rate of BCR to that of definitive LVI. If our observations are validated in an independent cohort, consideration should be given to the inclusion of equivocal LVI as part of routine pathological reporting.